Reputations for Safety: Market Performance and Policy Remedies - Carmichael, H. Lorne (Journal of Labor Economics, 1986)
This paper examines the provision of industrial safety in a competitive labor market under the assumption that it takes time for workers to learn about changes in safety levels at a firm. It is shown that safety will in general be underprovided and that in some cases government-enforced workmen's compensation can bring improvements. The results hold even though in equilibrium all workers are perfectly informed about the level of safety prevailing at each firm and each is free to move to any firm he likes.